Assessment of genetic diversity and relatedness of local banana (Musa spp.) cultivars in Malaysia using simple sequence repeat (SSR) markers - Sharmilah Vetaryan,; Hooi, Wei Yeng; Lee, Yang Ping (Penerbit Universiti Kebangsaan Malaysia, 2024)
Banana (Musa spp.) is an economically important crop widely consumed all over the world. Understanding the genetic diversity and relatedness between various banana cultivars is important to continuously improve its fruit characteristics, nutritional value, and disease resistance. This study aimed to develop a DNA fingerprinting panel using polymorphic simple sequence repeat (SSR) markers for the genetic characterisation of 11 banana cultivars in Malaysia. A total of 10 polymorphic SSR markers were developed into a multiplex PCR reaction and capillary electrophoresis to uniquely profile our collection of banana cultivars. The developed fingerprinting panel successfully amplified a total of 95 alleles, with 6 to 13 alleles per SSR marker. The average SSR marker polymorphic information content (PIC) value is 0.812, indicating the informativeness of the panel. Analysis of molecular variance (AMOVA) shows that 97% of the molecular variance from our banana collection is due to inter-variety genetic diversity, while the remaining 3% is due to intra-variety genetic diversity. A population structure analysis groups our collection of banana varieties according to the presence of at least one M. balbisiana (B) genome in their genetic makeup. The Cavendish variety, however, showed a distinct structure compared to the other cultivars. This SSR fingerprinting panel provides valuable insights into the genetic diversity and relatedness between banana cultivars in Malaysia. It has the potential to assist future banana breeding initiatives and serve as an effective quality control measure for verifying varieties in a tissue culture facility involved in banana planting materials production.